Legislative and Judicial Dynamics of Setting the Quota for Women's Representation in Parliament in the 2024 General Elections - I Komang Adi Muliana (University of Jember, Indonesia, 2024)
The policy choice of regulating women's quota by the General Election Commission through PKPU Number 10 of 2023 (PKPU 10/2023) has caused debate among democracy observers, especially those who care about women's representation in parliament. This study aims to analyze the compatibility of PKPU Number 10 of 2023 with the Election Law and analyze the Supreme Court Decision Number 24 P/HUM/2023 regarding the material testing of Article 8 paragraph (2) PKPU 10/2023. The method used in the study is normative research with a statutory approach and a case approach. The results of this study show that there are differences between the quota for women's representation in PKPU 10/2023 and the Election Law. When viewed in terms of its formation, PKPU 10/2023 was made with the choice of authoritarian political configuration and is characterized as a conservative legal product. The results also justify the first discussion through the annulment of the provisions of Article 8 paragraph (2) PKPU 10/2023 through the Supreme Court Decision Number 24 P/HUM/2023. The conclusion of this study shows the incompatibility of women's quota arrangements regulated by the KPU, but this has been corrected through the Supreme Court's decision. The results of this study are also a contribution of thought for policymakers to always harmonize regulations in every legislative process.